Characterization of Mungbean CONSTANS-LIKE Genes and Functional Analysis of CONSTANS-LIKE 2 in the Regulation of Flowering Time in Arabidopsis - Liu, Chenyang; Zhang, Qianqian; Zhu, Hong; Cai, Chunmei; Li, Shuai (Frontiers in Plant Science, 2021)
CONSTANS-LIKE (COL) genes play important roles in the regulation of plant growth and development, and they have been analyzed in many plant species. However, few studies have examined COL genes in mungbean (Vigna radiata). In this study, we identified and characterized 31 mungbean genes whose proteins contained B-Box domains. Fourteen were designated as VrCOL genes and were distributed on 7 of the 11 mungbean chromosomes. Based on their phylogenetic relationships, VrCOLs were clustered into three groups (I, II and III), which contained 4, 6 and 4 members, respectively. The gene structures and conserved motifs of the VrCOL genes were analyzed, and two duplicated gene pairs, VrCOL1/VrCOL2 and VrCOL8/VrCOL9, were identified. A total of 82 cis-acting elements were found in the VrCOL promoter regions, and the numbers and types of cis-acting elements in each VrCOL promoter region differed. As a result, the expression patterns of VrCOLs varied in different tissues and throughout the day under long-day and short-day conditions. Among these VrCOL genes, VrCOL2 showed a close phylogenetic relationship with Arabidopsis thaliana CO and displayed daily oscillations in expression under short-day conditions but not long-day conditions. In addition, overexpression of VrCOL2 accelerated flowering in Arabidopsis under short-day conditions by affecting the expression of the flowering time genes AtFT and AtTSF. Our study lays the foundation for further investigation of VrCOL gene functions.